Calcitonin gene-related peptide monoclonal antibodies for migraine prevention: comparisons across randomized controlled studies - Mitsikostas, Dimos D; Reuter, Uwe (Current opinion in neurology, 2017)
The results of phase 2 randomized controlled trials for the prevention of episodic and chronic migraine demonstrating the efficacy and safety of four mAbs targeting the calcitonin gene-related peptide (CGRP) pathway [ALD403 (eptinezumab), AMG334 (erenumab), LY2951742 (galcanezumab) and TEV48125 (fremanezumab)] have been published recently, and phase 3 trials are in process. This development will change headache management fundamentally. We aim to summarize and compare the phase 2 data. The change from baseline in the number of migraine days at the end of treatment in high-frequency episodic migraine was -1 (at weeks 5-8), -1.1 (at weeks 9-12), -1.2 (at weeks 9-12) and -2.6 (at weeks 9-12) days for ALD403, AMG344, LY2951742 and TEV48125 (225 mg), respectively. Number needed to treats for responders and odds ratio for any adverse event were 4.7, 6.2, 4.0 and 4.0 and 1.09, 0.96, 1.07 and 1.05, respectively. All four CGRP antibodies display comparable efficacy that does not differ significantly from that of the currently available oral antimigraine drugs. However, their safety and tolerability profiles as well as low frequency of administration looks promising but remains to be verified in long-term and large-scale trials. Considerations related to pregnancy, risk for cardiovascular effects and cost are subject for further evaluation.